2019
DOI: 10.3390/molecules24010210
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Natural Bioactive Compounds from Hibiscus sabdariffa L. on Obesity

Abstract: Obesity is a condition associated with the accumulation of excess fat in the body, energy imbalance, lipogenesis, etc., which increases adipose tissue mass through adipogenesis and poses a health risk. Its prevalence has become an economic burden to the health care system and the world at large. One of the alternatives to tackling obesity involves the use of bioactive compounds. We critically examined the effects of Hibiscus sabdariffa extract (HSE) on various parameters associated with the development of obes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
74
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 89 publications
1
74
0
7
Order By: Relevance
“…Accumulating evidence suggested that abundant bioactive compounds found in H. sabdariffa are responsible for its health‐promoting function (Ojulari, Lee, & Nam, ). Yang et al (Yang et al, ) reported that H. sabdariffa polyphenols exhibited more potency to reduce cholesterol than the crude extract, and its mechanism is associated with AMPK activation and SREBP‐1 reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggested that abundant bioactive compounds found in H. sabdariffa are responsible for its health‐promoting function (Ojulari, Lee, & Nam, ). Yang et al (Yang et al, ) reported that H. sabdariffa polyphenols exhibited more potency to reduce cholesterol than the crude extract, and its mechanism is associated with AMPK activation and SREBP‐1 reduction.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanism of obesity mediated by cytokines, adiponectin, and leptin has been correlated with increasing inflammation and oxidative stress, and leads to the development of metabolic diseases including certain types of cancer; hyperglycemia; type 2 diabetes; high blood pressure; and liver, heart, and gallbladder diseases [2,7]; which pose major health risks globally [8]. Specifically, obesity and type 2 diabetes are associated with an increase in oxidative stress and inflammation in adipose tissues [2,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, obesity and type 2 diabetes are associated with an increase in oxidative stress and inflammation in adipose tissues [2,9,10]. Consequently, researchers have been exploring functional materials of plant origin that contain antioxidants to combat obesity and its comorbidities, as alternatives to conventional approaches that have been adopted previously-including surgery and anti-obesity drugs, which do not often have enduring effects and have side effects including headaches, excessive thirst, insomnia, constipation, and steatorrhea [11], or may have yo-yo effects [8,12]. Therefore, the consideration of antioxidants as therapeutic agents in the treatment and/or prevention of obesity and its comorbidities would be insightful.…”
Section: Introductionmentioning
confidence: 99%
“…The edible calyces can be made into jam, jelly, sauce, and wine; its seeds contain high protein and are used as a food ingredient in Africa . Bioactive ingredients of H. sabdariffa , such as anthocyanins, anthocyanidins with a sugar moiety, gallic acid, syringic acid, caffeic acid, and flavonoids have been widely studied for their antimicrobial, plasma‐cholesterol reducing, and immune‐regulating functions . Studies have also reported that extracts from H. sabdariffa inhibit cancer cell metastasis .…”
Section: Introductionmentioning
confidence: 99%
“…12 Bioactive ingredients of H. sabdariffa, such as anthocyanins, anthocyanidins with a sugar moiety, gallic acid, syringic acid, caffeic acid, and flavonoids have been widely studied for their antimicrobial, plasma-cholesterol reducing, and immune-regulating functions. [13][14][15][16] Studies have also reported that extracts from H. sabdariffa inhibit cancer cell metastasis. 17,18 It is known that flavonoids inhibit oxidative stress in vitro by acting either as free radical scavengers or as metal chelating agents.…”
Section: Introductionmentioning
confidence: 99%